Antiobesity and Lipid Lowering Activitiy of Vigna unguiculata (L) Walp. Seed in High Fat Diet Induced Obese Mice - Md. Saddam Hussain; Mohammad Salim Hossain; Md. Mamun Or Rashid (Journal of Pharmacy and Nutrition Sciences, 2019)
Seed of Vigna unguiculata is commonly used as culinary in Bangladesh and many parts of the world. Besides this, seed of V. unguiculata possesses some medicinal values like being an antioxidant etc. In this study, seeds of V. unguiculata were used to determine the link between its total phenolic content and lipid lowering activity. Phytochemicals presents in the seeds were evaluated. Total phenolic content (TPC) was determined by using folin-ciocalteu method. High fat diet induced obese mice were used for anti-obesity and antihyperlipidemic test. Body weight gain, total cholesterol and triglyceride levels were analyzed. Preliminary phytochemical screening showed that amino acid, phenol, alkaloid and terpenes were very strongly present in cowpea seed, while carbohydrate, cardiac glycoside, was moderately present. The V. unguiculata seeds showed significant total phenolic content with a value of 119.716mg of GAE/gm equivalent. Cowpea seeds, with a dose of 400mg/kg body-weight, showed significant reduction in body weight gain when treated with fat diet compared with normal diet. Cowpea seeds are also capable of lowering the serum cholesterol (p < 0.01) and serum triglyceride level (p < 0.01) more significantly in high fat diet induced obesity. V. unguiculata seeds have a significantly high total phenolic content while the other phytochemicals are moderately present in them. It has anti-obesity activity that can interfere with serum cholesterol and triglyceride metabolism. So, it seems like a healthy diet for the management of obesity and other heart related disease.